2003
DOI: 10.1046/j.1439-037x.2003.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Row Spacing and Seeding Rate on Seed Yield and Yield Components of Forage Turnip (Brassica rapa L.)

Abstract: The effects of four row spacings (17.5, 35.0, 52.5 and 70.0 cm) and five seeding rates (50, 100, 200, 400 and 800 viable seeds m−2) on seed yield and some yield components of forage turnip (Brassica rapa L.) were evaluated under rainfed conditions in Bursa, Turkey in the 1998–1999 and 1999–2000 growing seasons. Plant height, stem diameter, pods/terminal raceme, total pods/plant, seeds/pod and primary branches/plant were measured individually. The number of plants per unit area was counted and the lodging rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
(21 reference statements)
5
12
1
Order By: Relevance
“…It was found that C 2 produced maximum number of seed yield as compared C 1 . These results are lined with [2] [3] [14] [15] [17].…”
Section: Seed Yieldsupporting
confidence: 70%
“…It was found that C 2 produced maximum number of seed yield as compared C 1 . These results are lined with [2] [3] [14] [15] [17].…”
Section: Seed Yieldsupporting
confidence: 70%
“…Koocheki and Marashi (1989) concluded that decreasing density caused less plant competition on lights, nutritious and humidity, so plants with more stem and leaf were produced, after it, they themselves produced more flower and pod, but Askarian et al (1995) told that seed rate had not meaningful effect on pod number of raceme. Also, another research by Bilgili et al (2003) on rows space and seed rate treatments on Brassica rapa: Showed that pod number in main stem hadn't effected by space between rows, but pod number in plant increased by increasing row space obviously and decreased by increasing seed rate.…”
Section: Pod Number Per Racemementioning
confidence: 99%
“…In the United States, fruit production ranged from 19 to 187 pods plant (1 in a naturalized B. rapa population in California (Agren and Schemke 1994); seed production was not reported. As a crop in Turkey, B. rapa had 217 and 404 pods plant (1 with 10 to 11 seeds pod (1 , resulting in stable seed production over planting densities ranging from 50 to 800 seeds m (2 (Bilgili et al 2003). Seed production in domesticated B. rapa tends to be lower than in domesticated B. napus (Miller et al 2003).…”
Section: Historymentioning
confidence: 99%